Legal Regulation of Electronic Identity in eHealth Services in Poland and Estonia: A Comparative Analysis - Świtała, Krzysztof (Review of European and Comparative Law, 2026)
The primary aim of the article is to analyze the role of electronic identity in ICT-enabled healthcare in the context of existing legal instruments in these areas, both at the EU level and in the regulations of selected Member States (Poland, Estonia). A basic analysis of eHealth, telemedicine, and EHR systems was conducted, considering the role of electronic identity in data processing within the health care information infrastructure. EU regulations, such as eIDAS, the directive on patients’ rights in cross-border healthcare, and the regulation on the European Health Data Space were taken into account. The role of electronic identity management systems in the context of the patient’s right to medical services, consent, information about their condition, and the preservation of medical professional confidentiality and privacy is also discussed. Finally, existing electronic identification systems in Poland (Profil Zaufany, Profil Osobisty, mObywatel) and Estonia (e-ID), which are also used to authenticate patients accessing healthcare services in these countries, are presented.